2017
DOI: 10.1080/07434618.2017.1326066
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of key word signing in adults with intellectual disabilities: novel signed turns facilitated by partners’ consistent input and sign imitation

Abstract: The aim of the present study was to examine the relationship between the use of key word signing (KWS) by support staff and by adults with intellectual disabilities (clients) who had experience with using KWS. Specifically, we explored whether these clients were more inclined to use KWS when support staff used KWS or imitated signs. One-to-one conversations between 24 clients and their support staff were filmed and transcribed. Partner turns were coded for communication mode (spoken or signed) and KWS response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Nevertheless, staff seldom used KWS during these activities. Considering the positive association between the KWS usage of staff and adults with intellectual disabilities (Grove & McDougall, ; Rombouts et al, ), staff's limited use of signs may perhaps cause individuals with intellectual disabilities to also limit their use of signs during non‐communicative activities and mealtimes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, staff seldom used KWS during these activities. Considering the positive association between the KWS usage of staff and adults with intellectual disabilities (Grove & McDougall, ; Rombouts et al, ), staff's limited use of signs may perhaps cause individuals with intellectual disabilities to also limit their use of signs during non‐communicative activities and mealtimes.…”
Section: Discussionmentioning
confidence: 99%
“…After direct support staff modelled and prompted KWS, individuals with intellectual disabilities increased their use of KWS (Schepis et al, ; Carter, ; Meuris et al, ). In cross‐sectional studies, a positive association was found between the use of manual signs by individuals with intellectual disabilities and staff (Grove & McDougall, ; Rombouts et al, ). Research also suggests that adults with intellectual disabilities may be more encouraged to use KWS when partners imitate manual signs (Rombouts et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During semi‐structured one‐to‐one conversations, adults with ID were significantly more likely to respond with a signed rather than exclusively verbal exchange immediately after staff had used a sign (Rombouts et al . ). Because of the semi‐structured set‐up in that study, the results could not be generalised to a naturalistic setting where group activities are more common than one‐to‐one conversations.…”
Section: Introductionmentioning
confidence: 97%